An Empirical Study of Factors Affecting Mobile Wireless Technology Adoption for Promoting Interactive Lectures in Higher Education - Gan, Chin Lay; Balakrishnan, Vimala (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Use of mobile technology is widespread, particularly among the younger generation. There is a huge potential for utilizing such technology in lecture classes with large numbers of students, serving as an interaction tool between the students and lecturers. The challenge is to identify significant adoption factors to ensure effective adoption of mobile technology to promote interactivity between students and lecturers. This paper aims to examine factors supporting the use of mobile wireless technology during lectures to promote interactivity between students and lecturers in Malaysia’s higher education institutions. A survey involving higher education students enrolled in on-campus academic courses in Malaysia was conducted with a sample size of 302. Factor analysis results identified five factors: independent variables System Usefulness (SU), User System Perception (USP), User Uncertainty Avoidance (UUA), System and Information Quality (SIQ), and dependent variable Mobile Wireless Technology Adoption for Interactive Lectures (MWT_AIL). All independent variables are positively associated to MWT_AIL, with UUA and SIQ having higher levels of significance compared to SU and USP. Respondents were selected from higher learning institutions from urban areas in Malaysia. Therefore results obtained are not representative of the entire higher education landscape in Malaysia, and future studies are warranted to include higher learning institutions located in rural areas. It is hoped that findings from this study will serve as a catalyst for future studies to be conducted, particularly among higher education researchers seeking ways to utilize technology effectively to enhance the learning experiences of students.